Genomic Effects Associated With Response to Placebo Treatment in a Randomized Trial of Irritable Bowel Syndrome - Wang, Rui-Sheng; Lembo, Anthony J.; Kaptchuk, Ted J.; Cheng, Vivian; Nee, Judy; Iturrino, Johanna; Rao, Meenakshi; Loscalzo, Joseph; Silvester, Jocelyn A.; Hall, Kathryn T. (Frontiers in Pain Research, 2022)
Background and Aims: Irritable bowel syndrome (IBS), a functional pain disorder of gut-brain interactions, is characterized by a high placebo response in randomized clinical trials (RCTs). Catechol-O-methyltransferase (COMT) rs4680, which encodes high-activity (val) or low-activity (met) enzyme variants, was previously associated with placebo response to sham-acupuncture in an IBS RCT. Examining COMT effects and identifying novel genomic factors that influence response to placebo pills is critical to identifying underlying mechanisms and predicting and managing placebos in RCTs. Methods: Participants with IBS (N = 188) were randomized to three placebo-related interventions, namely, double-blind placebo (DBP), open-label placebo (OLP), or simply trial enrollment without placebo treatment [no placebo (i.e., no pill) treatment control (NPC)], for 6 weeks. COMT rs4680, gene-set, and genome-wide suggestive (p < 10−5) loci effects on irritable bowel symptom severity score (IBS-SSS) across all participants were examined. Results: Participants with IBS homozygous for rs4680 met (met/met) had the greatest improvement across all arms, with significantly greater improvement compared to val/val in DBP (beta (SE), −89.4 (42.3); p = 0.04). Twelve genome-wide suggestive loci formed a gene regulatory network highly connected to EGR1, a transcription factor involved in placebo-related processes of learning, memory, and response to stress and reward. EGR1 gene expression in peripheral blood mononuclear cells (PBMC) was significantly reduced at the endpoint across all treatment arms (log fold-change, −0.15; p = 0.02). Gene-set enrichment analysis returned three genome-wide significant ontology terms (GO:0032968, GO:0070934, and GO:0070937) linked to transcription regulation and GO:0003918 associated with DNA topoisomerase regulation. Conclusion: These results suggest common molecular mechanisms in response to varying forms of placebo that may inform personalized IBS treatment and placebo response prediction. Clinical Trial Registration:ClinicalTrials.gov, Identifier: NCT0280224.